A Study on Knowledge of Pulmonary Tuberculosis and DOTS among Pulmonary Tuberculosis Patients in West Tripura District, India (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2016)
Introduction: A study was conducted for six randomly selected designated Microscopy Centre areas of West Tripura District of India with objectives to assess the knowledge regarding Pulmonary Tuberculosis (PTB) and DOTS among the PTB patients and to identify the factors determining the knowledge.Methodology: This cross-sectional study was conducted among 220 PTB patients registered for treatment with DOTS therapy during July 2011 to June 2012.Results: The study showed that 29.10% of the patients had satisfactory knowledge of the disease and its treatment. Only 14.10% patients had the correct knowledge regarding the cause of the disease and 53.60% of the patients had the knowledge regarding the mode of transmission and measures for prevention. Again, 6.40% of the patients had the knowledge regarding the drug dosage schedule and 52.70% patients knew the duration of treatment. Satisfactory knowledge was found to be significantly higher among patients with education level of Higher Secondary or above, and patients who had prior knowledge of tuberculosis [OR-17.60(1.68-183.90)]. Again patients who had less income had 86% [OR-0.14 (0.03-0.64)] less chance of having satisfactory knowledge.Conclusion: The overall knowledge level among the patients is unsatisfactory and there is urgent need of advocating educational activities among the patients.SAARC J TUBER LUNG DIS HIV/AIDS, 2015; 12(1), Page: 1-7